Lateral Epicondylitis: Bridging Clinical Assessment and Imaging in Diagnosis and Management - A Review of Current Evidence - Grylowska, Gabriela; Paluch, Anna; Adamczyk, Aleksandra; Żak, Agata; Gunia, Katarzyna; Palak, Andrzej; Rebizant, Marcin; Banasik, Mateusz; Ignatowicz, Anna; Tryba, Michał (Quality in Sport, 2026)
Background. Lateral epicondylitis (tennis elbow) is an overuse tendinopathy of the wrist extensors associated with repetitive gripping and wrist extension. It is a common cause of lateral elbow pain and functional impairment. The condition is currently regarded as predominantly degenerative, although inflammatory features may be present at the initial stage of the disease. Aim. The aim of this study was to review current evidence on the histopathology, diagnosis, and role of imaging in the evaluation and differential diagnosis of lateral epicondylitis, with consideration of main treatment approaches. Material and methods. A literature search was conducted using databases such as PubMed and Google Scholar. The review included peer-reviewed articles focusing on lateral epicondylitis, its histopathology, clinical presentation, diagnostic methods, and imaging techniques, including ultrasound and magnetic resonance imaging. Results. Clinical history and physical examination, including provocation tests and assessment of grip strength, remain the cornerstone of diagnosis. Differential diagnosis is essential due to the proportion of misdiagnosed cases. Imaging studies play a complementary role - ultrasonography allows for dynamic assessment and identification of tendon abnormalities, while MRI enables a more detailed evaluation of intra-articular structures and the extent of tissue damage. Radiography (X-ray) and computed tomography arthrography (CTA) are mainly used in selected cases. Conclusions. Lateral epicondylitis requires a comprehensive diagnostic approach based primarily on clinical assessment, supplemented by imaging when necessary. Ultrasonography represents the primary imaging modality for evaluating this condition, whereas magnetic resonance imaging is particularly useful in cases requiring more in-depth assessment and in treatment planning.